Gambaran Kyouiku Mama pada Film Sakurairo No Kaze Ga Saku - Tia Martia; Metty Suwandany; Yasmin Fatimatuzahirah B; Bintang Calista Pebriana (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Kyouiku mama is the consept in Japanese society which means the mother of educators, a mother who seeks to form the character of her child through formal and nonformal education (physical, social and emotional). This research aims to describe the concept of kyouiku mama in the film Sakurairo no kaze ga saku directed by Junpei Matsumoto. The film is based on the true story of Satoshi Fukushima who has been a professor at the University of Tokyo’s Research Center for Advanced Science and becoming the first deafblind person. This research is a qualitative study with descriptive methods of analysis. The data collection is collected by tapping/recording techniques, Simak Bebas Libat Cakap” technique (Uninvolved Conversation Observation Technique) and through literature research. Record the dialogue and sort out the images which suit the problem. The results of the research show the concept of kyouiku mama which was successfully described by Reiko as the mother of Satoshi, a child with special needs/disabilities who are deaf-blind person. Reiko found a way to communicate with Satoshi by finger braille or 指点字/ yubi tenji.